Local and systemic 20S proteasome release in patients with stenting of stenotic saphenous vein bypass grafts – a pilot study - Sixt, Stephan Urs; Leineweber, Kirsten; Böse, Dirk; Konorza, Thomas; Haude, Michael; Hogrebe, Stephan; Kleinbongard, Petra; Erbel, Raimund; Peters, Jürgen; Heusch, Gerd (Archives of Medical Science, 2009)
Introduction: The ubiquitin-proteasome system is involved in the development and progression of atherosclerosis. We tested the release of local and systemic proteasome in patients with advanced coronary artery disease. Material and methods: Thirty-nine symptomatic male patients (68 ±1 years) with a flow-limiting stenosis (63 ±1% diameter reduction) in their saphenous vein aortocoronary bypass graft (SVG) underwent stent implantation under protection with a distal balloon device, which permits aspiration of the plaque-derived particulate debris and fluid; the 20S proteasome concentration was measured in the venous plasma of 28 healthy controls and of these 39 patients as well as in the soluble and particulate fraction of the aspirate before and after stenting, using an enzyme-linked immunosorbent assay. Results: The peripheral venous 20S proteasome plasma concentration was higher in patients undergoing SVG stenting (1327 ±102 ng/ml) than in healthy subjects (447 ±29 ng/ml, p median of 1335 ng/ml: 40 ±9% diameter reduction within 6.0 ±0.4 months, n = 20 stenoses vs. Ł 1335 ng/ml: 17 ±3% diameter reduction within 6.4 ±0.5 months, n = 21 stenoses, p = 0.0059). 20S proteasome concentration in the particulate debris fraction averaged 7010 ±890 ng/ml. However, the plaque-derived 20S proteasome concentration during intervention was less in patients with high (> 1335 ng/ml) venous 20S proteasome concentration (5846 ±993 ng/ml, n = 21 stenoses) than in those with lower (Ł 1335 ng/ml) concentration (8538 ±1548 ng/ml, n = 22 stenoses, p = 0.0308). Conclusions: We propose that release of 20S proteasome from an atherosclerotic lesion may reflect progression of coronary atherosclerosis and could possibly serve as a biomarker.